Sequence architecture and sedimentary characteristics of a Middle Jurassic incised valley, western Sichuan depression, China - Jun-Long Liu (KeAi Communications Co., Ltd., 2018)
Abstract The Middle Jurassic Shaximiao Formation encompasses tens of meters of thick lowstand meandering valley (LMV) strata in the western Sichuan foreland basin. Ancient LMVs newly discovered in this area were further studied based on sequence stratigraphy and seismic sedimentology. The aim of the present study was to investigate the sedimentary characteristics, sequence architecture, and the controls on LMV deposition in this tectonically active basin using field survey data, seismic sections, seismic amplitude imaging, core description, and comprehensive application of drilling data. The results show the following: (1) Three regional sequence boundaries and two flooding surfaces were recognized, and the Shaximiao Formation was divided into two-third-order sequences and four systems tracts. (2) Three sedimentary facies associations were identified: incised valley-fill, tributary channel, and overbank facies. Incised valleys are 5–17 km wide, 20–60 m deep and traceable for 120 km along their axes. (3) In the downstream segment, the role of tectonism gradually diminishes, and periodic base-level changes control the form and evolution of the incised valleys. Three types of LMVs—A1, A2, and A3—developed with changes in base level (lake level); of these types, the base level of the A3 LMV was likely the lowest.